Substance-Induced Bipolar Disorder: A Comprehensive Case Study of a 24-Year-Old Male - Abdul Ghaffar, Aqsa; Aslam, Farzana (University of Wah Journal of Social Sciences, 2024)
This case study examines a 24-year-old male diagnosed with Substance-Induced Bipolar and Related Disorder (Severe). The patient presented with a history of excessive drug use, mood elevation, irritability, and various manic symptoms. A detailed psychological assessment was conducted, leading to a comprehensive treatment plan. The patient exhibited significant improvement following an integrated therapeutic approach. This report discusses the complexities of diagnosing and treating substance-induced mood disorders, highlighting the need for a holistic treatment approach that addresses both substance use and mental health issues.